The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.17221/45/2021-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Association of leaf chlorophyll content with the stay-green trait and grain yield in wheat grown under heat stress conditions

Abstract: Heat stress is a major production constraint of wheat in South Asia, particularly in the Gangetic plains of India and Bangladesh. The leaf chlorophyll status is a key determinant for a high rate of photosynthesis under stress. The present experiments included 238 genotypes in 2016–2017 and 321 genotypes in 2017–2018 under optimum and under heat stress conditions. Subsequently, a set of 100 genotypes selected on basis of the heat susceptibility index was evaluated in 2018–2019 under heat stress conditions to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
(38 reference statements)
2
5
0
Order By: Relevance
“…These results show that NDVI can use to estimate the grain yield. Similar results were reported by Roy et al (2021), Marti et al (2007), Sultana et al (2014), Morgounov et al (2014), Mekliche et al (2015).…”
Section: Normalized Difference Vegetation Indexsupporting
confidence: 90%
See 1 more Smart Citation
“…These results show that NDVI can use to estimate the grain yield. Similar results were reported by Roy et al (2021), Marti et al (2007), Sultana et al (2014), Morgounov et al (2014), Mekliche et al (2015).…”
Section: Normalized Difference Vegetation Indexsupporting
confidence: 90%
“…The highest SPAD values was obtained from centre of Konya followed by İçeri Çumra and Gözlü locations respectively with 48.28, 47.36 and 44.13 (Table 3). As reported by some researchers like Roy et al (2021), there were differences in SPAD values among genotypes. The highest SPAD (51.64) was recorded on Genotype 3 (Karahan 99) (Table 4).…”
Section: Soil Plant Analysis Developmentsupporting
confidence: 61%
“…The SG trait is an important character that enables the plant to better adapt under high temperatures by providing assimilates to the developing grain for a longer period as compared to the non-SG trait. Genotypes showing SG traits are associated with a delayed leaf senescence rate and increased yield (Christopher et al 2008;Chen et al 2018;Sui et al 2019;Roy et al 2021). Plant growth regulator (PGR) brings physiological adaptations in response to heat stress, including the interactive effects and cross-talk of various PGRs on plant physiological and biochemical mechanisms (Sabagh et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…During the reproductive stage, colder canopies were linked to higher aerial biomass, more grains, and higher yields in wheat (Rebetzke et al 2012;Lepekhov 2022). Many reports have suggested that low CT under heat stress can advance yields (Amani et al 1996;Balota et al 2007;Rutkoski et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In rice, grain Zn concentrations depend on plants’ ability to redistribute Zn from older leaves and stems, as well as phloem mobilization of Zn ( Wu et al, 2010 ). Significant contributions of the flag and penultimate leaves to wheat grain yield have been observed ( Roy et al, 2021a ), but there are no detailed studies concerning the proportionate remobilization of Zn and Fe from different wheat plant parts. Uauy et al (2006) observed an abundance of Zn, Fe and proteins in wheat flag leaves during grain filling, in plants carrying the Gpc-B1 locus.…”
Section: Increase Zn and Fe In Wheat Endospermmentioning
confidence: 99%